GENEOLOGY OF AUTHORITY AND THE PUZZLE OF SOVEREIGNTY - Matiashvili, Lasha (European Scientific Journal, ESJ, 2016)
In the following article on the basis of Agamben’s and Arendt’s philosophical tradition the idea of authority will be examined and interpreted in the light of the Agamben’s most provocative and crucial concept-idea of Homo Sacer. Genuine understanding of the concept will be attempted by using genealogical and hermeneutical method. Despite the historical and philosophical richness and depth of material, Arendt’s investigation lacks precise definition of the term and also nothing is said about the place and function of authority in modern social and political context. Arendt confines herself with historical elucidation and negative representation of authority. She tells more about what was not its meaning, rather defining it in positive terms. However, opposite can be said on Giorgio Agamben. Methodological resemblance of authors is evident, both chose archeological and historical form of inquiry, but as Agamben characterized his attitude, his aim was to develop the problematic thought and to say what remains unsaid and concealed in other’s writings without any ambition of fulfilling it. Therefore, we can interpret the notions of authority and power, as they are mixed with each other in the sovereign’s figure of indifference.